The Role of Islamic Religious Education Teachers in Transforming the Culture of Resignation Towards Natural Disasters in Indonesia - Faqihuddin Achmad; Fauzan Ilyasa Faisal; Husniah Lu’lu’; Rahardja Muhammad Nurfaizi Arya; Rambe Anggi Afrina; Dwietama Regita Ayu; Putri Annisa Ningtias Cevie (E3S Web of Conferences)
Indonesia is a country frequently confronted with natural disasters, positioning it as a nation intimately familiar with such challenges. Studies indicate that a notable segment of the Indonesian population approaches the unpredictability of natural phenomena with a ’let’s see what happens’ attitude, often described as ’Cultural Resignation.’ This perspective is characterized by deferring all outcomes to a divine will, while underestimating the importance of human initiative. This research aims to explore the influence of Islamic Religious Education teachers in transforming this culture of resignation that prevails in the context of disasters. To achieve this, interviews will be conducted with a diverse group of 50 IRE teachers across various educational levels, including elementary, junior high, and high schools. The data collected will be analyzed using NVIVO 12 software, with the goal of identifying the critical role that IRE teachers play in promoting a more proactive and adaptive approach to managing disasters. The results of this study are expected to provide significant insights into the positive changes that Islamic Religious Education teachers can bring about in society’s views and attitudes towards disaster preparedness and response, highlighting the vital role of disaster mitigation-focused Islamic Religious Education.